Evaluating the Enterprise Resource Planning (ERP) System of a Bread Manufacturing Organisation from the Perspectives of Stakeholders - Chan, Yvonne; Chin, Shy Wei (Journal of Techno-Social, 2022)
Enterprise Resource Planning (ERP) framework integration is an important and foundational business process preparation and knowledge sharing process. The ERP framework has in the past decade been regarded as a vital enabler for organizational performance and functions as an integral feature in today's diverse and competitive market climate. It normally needs considerable feedback in terms of commitment, time, and resources to incorporate an ERP method. In recent research, numerous contributing factors to the ERP's performance or failure were more specifically demonstrated; still, only the ERP's contributions in developed countries were illuminated. Moreover, many developing countries are interested in ERP deployment in their organizations. As Microsoft Dynamics 365 has not been thoroughly researched to date, this study seeks to penetrate an unexplored territory for Malaysia by concentrating on Malaysia-specific results. The importance of this analysis is a detailed review of the spectrum of Microsoft Dynamics 365 operations in supply chain management. Additionally, this analysis aims to help specific sectors and enterprises further grasp the value of Microsoft Dynamics 365 as an enterprise resource planning (ERP) solution. A reasonable amount of evidence would be supplied that addresses the feasibility, usefulness, and practicality of Microsoft Dynamics 365. This research aimed to discover variables that impact ERP users in an ERP environment, with the intention of gaining a more detailed understanding of the end-user ERP output through a qualitative case study. It is important to recognize all of the influences on the stakeholders in the ERP management and in this study, the Microsoft Dynamic 365 (D365) was the target system. The study utilized a qualitative research framework that combines computational techniques and mathematical estimation for data collection and interpretation. The ERP data obtained are the data required for answering the study questions. The findings of this study show the importance of stakeholders and ERP Framework as well as ERP system such as D365 in promoting individual ERP successes. The researcher also looked at the views of stakeholders on the impact of system quality. This relationship was investigated from the viewpoints of the end-users, stakeholders.  Understanding the relative value of the information system factors places an emphasis on the vital performance factors perceived by end consumers by organizations and suppliers. In general, the conclusion from the analysis is that the management of the supply chain in extended companies should not expect too much of an ERP system as eventually still needs various customization within certain industries. This study has helped to reduce the discrepancy in the theory of stakeholders regarding the criteria for the selection of systems and methods for bread production in Malaysia, although some of the criteria and methods provided for in the theories might not be prominent in the real world. Practitioners tend to respect and comply with the requirements of the organization over the more sophisticated ERP scheme.